2013
DOI: 10.2298/jmmb120806024h
|View full text |Cite
|
Sign up to set email alerts
|

Sulphuric acid leaching of low/medium grade managanese ores using a novel nitrogeneous reductant-NH3NH2HSO4

Abstract: Low and medium grade land as well sea based manganese ores were used for manganese extraction in H2SO4 - NH3NH2HSO4 (hydrazine sulphate) medium For land based Mn ores, only Mn recovery is important but for sea nodules which contain substantial amounts Co, Ni, and Cu, their recovery is equally important. In the present studies four samples used were: Indian ocean manganese nodules, medium and low grade Mn ores of Gujarat, and low grade Mn ore of Orissa, India. The Mn content of these ores varied from 15 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Some metal recovery experiment was also carried out by using salts as lixiviants. For instance, to extract nickel, copper, and cobalt from their metal oxide form, ferric chloride (FeCl 3 ) salt was engaged as lixiviant, as reported by Hariprasad and their research team . Results showed that 28% Ni, 92% Cu, and 24% Co were recovered from converter slag, meanwhile, 77%, 54%, and 44% recovery was achieved for Ni, Cu, and Co, respectively, from smelter slag.…”
Section: Metal Recovery Techniquesmentioning
confidence: 99%
“…Some metal recovery experiment was also carried out by using salts as lixiviants. For instance, to extract nickel, copper, and cobalt from their metal oxide form, ferric chloride (FeCl 3 ) salt was engaged as lixiviant, as reported by Hariprasad and their research team . Results showed that 28% Ni, 92% Cu, and 24% Co were recovered from converter slag, meanwhile, 77%, 54%, and 44% recovery was achieved for Ni, Cu, and Co, respectively, from smelter slag.…”
Section: Metal Recovery Techniquesmentioning
confidence: 99%
“…La solución de lixiviación química (en condiciones estáticas) fue preparada con de H 2 SO 4 al 4% (Hariprasad et al, 2013) en cada sistema de columna por gravedad, con similares medidas descritas en el sistema anterior. …”
Section: Estudio De Lixiviación Químicaunclassified
“…The remaining unreacted MnO 2 can only be dissolved in the presence of a reductant such as SO 2 (g) or hydrazine [20,21], of which the reaction can be represented as:…”
Section: Introductionmentioning
confidence: 99%